Analyzing the Impact of Domestic and Global Monetary Policy on the Jakarta Composite Index (JCI): A Study of Post-Pandemic Market Response Anomalies - Moh. Fajar Prima Mukti; Fanlia Adiprimadana Sanjaya; Zakky Zamrudi (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to analyze the influence of inflation, the BI Rate, and the Fed Rate on the Jakarta Composite Index (JCI) for the 2021-2025 period. This study uses a quantitative causal associative method with an ex post facto design. The research sample consists of 60 monthly time-series secondary data observations tested using multiple linear regression with the Newey-West HAC Standard Errors method using Stata 14 software as a corrective measure to address autocorrelation issues. The results show that simultaneously, inflation, the BI Rate, and the Fed Rate significantly influence the JCI movement. Partially, the inflation rate is proven to have no significant effect on the JCI due to its relatively stable and controlled movement during the observation period. The BI Rate has a negative and significant effect on the JCI, confirming that an increase in the domestic benchmark interest rate will depress the stock index as investors shift their funds to fixed-income instruments. Conversely, the Fed Rate has a positive and significant effect on the JCI, where the increase in US interest rates is interpreted as a strong signal of global economic expansion and recovery, boosting market optimism. The ability of these three variables to explain variations in the JCI is 42.44% (based on the Adjusted R-squared value), while the remaining 57.56% is influenced by other factors outside the research model.